ANALISIS POLA KONSUMSI PANGAN RUMAH TANGGA MISKIN DI PROVINSI JAWA TIMUR - Dewi Mayasari; Iswan Noor; Dias Satria (EP FEB UNS, 2018)
Consumption pattern can reflect the level of wellbeing, where the higher expenditure for food commodities represents lower level of welfare. The objectives of this article are analyze the influence of socio economic characteristics in influencing poor household food consumption and analyze demand responses of poor household in East Java to food prices and income changes. Linear Approximation Almost Ideal Demand System (LA/AIDS) and elasticity are used to answer the objectives. The result showed that socio economic characteristics relatively contribute in determining food consumption patterns of poor household and based on their elasticity values, food commodities are price inelastic or basic necessity for poor households in East Java and income elasticity indicates no inferior goods found in poor households in East Java. Keywords: Consumption Patterns; LA/AIDS; Poor Households; East JavaJEL Clasification: C31, Q11